1975
DOI: 10.1128/aem.29.3.368-373.1975
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Survival in Laundered Fabrics

Abstract: Bacterial survival was determined in linens (i) inoculated with Staphylococcus aureus (ii), taken from hospital isolation patients' beds, and (iii) used by students in their homes. Two different washers using temperatures of 38, 49, 54 and 60 C, respectively, for different times were employed along with a commercial tumbler dryer. Findings, after macerating the linens in a Waring blender and enumerating on nonselective media, indicate that acceptable levels of survivors can be achieved in motel and hotel linen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 2 publications
0
30
0
Order By: Relevance
“…Although it is difficult to differentiate between the Sinner circle impact factors in many of the existing studies it is obvious that a higher washing temperature increases the logarithmic reduction (LR) of micro-organisms on a textile surface during laundering. Wiksell et al (1973) observed an LR increase of c. 2Á5 when shifting the temperature from 24°C to 68°C while Walter and Schillinger (1975) found the LR to be increased by 3 by raising the temperature from 38°C to 49°C. These studies were followed by many others showing a considerable effect of temperature on the reduction of micro-organisms (Arild et al 2003;Lichtenberg et al 2006;Bellante et al 2011;Linke et al 2011;Honisch et al 2014).…”
Section: Factors Influencing the Hygiene Efficacy Of Launderingmentioning
confidence: 97%
See 1 more Smart Citation
“…Although it is difficult to differentiate between the Sinner circle impact factors in many of the existing studies it is obvious that a higher washing temperature increases the logarithmic reduction (LR) of micro-organisms on a textile surface during laundering. Wiksell et al (1973) observed an LR increase of c. 2Á5 when shifting the temperature from 24°C to 68°C while Walter and Schillinger (1975) found the LR to be increased by 3 by raising the temperature from 38°C to 49°C. These studies were followed by many others showing a considerable effect of temperature on the reduction of micro-organisms (Arild et al 2003;Lichtenberg et al 2006;Bellante et al 2011;Linke et al 2011;Honisch et al 2014).…”
Section: Factors Influencing the Hygiene Efficacy Of Launderingmentioning
confidence: 97%
“…Interestingly, although the TAED-mediated activation of percarbonate or perborate is temperaturedependent and should work best at temperatures of above 40°C, an additional antimicrobial effect can already be observed at lower temperatures (Honisch et al 2014). Likewise, chlorine bleach was shown to enhance the antimicrobial efficacy of laundering by 3-4 orders of magnitude, even at low temperatures (Walter and Schillinger 1975;Christian et al 1983;Blaser et al 1984;Smith et al 1987).…”
Section: Factors Influencing the Hygiene Efficacy Of Launderingmentioning
confidence: 99%
“…Various bacteria can survive in laundry even when the clothes are dry, and some of them can cause malodour. [43][44][45][46][47] For example, Munk et al reported malodour problems on fabrics, derived from both bacterial and enzymatic factors, in Europe and America. [44,48] They analysed laundry malodours and reported the washing efficiency based on the levels of the identified malodorous compounds (ethyl butanoate, (Z)-4-heptenal, (E)-2-nonenal, isovaleric acid, guaiacol and 4-methyloctanoic acid) found.…”
Section: Malodours In Laundrymentioning
confidence: 99%
“…It has been demonstrated (McNeil & Chopper 1962;Wiksell et al 1973;Buford et al 1977) that appreciable numbers of organisms may be transferred from contaminated to uncontaminated linen when these are included in the same wash cycle and also between linens washed in separate cycles where transfer of contamination is probably effected by organisms adhering to the washer surfaces. Although the studies by Walter & Schillinger (1975) indicate little value in the use of hypochlorites, Wilkhoff et al (1971) and Buford et al (1977) have demonstrated that addition of quaternary ammonium, phenolic disinfectants or hypochlorites to machine-wash cycles will produce significantly greater reduction in the numbers of viable organisms present in fabrics and in the water used for washing them than can be achieved by use of hot water and detergent alone. It is therefore suggested that disinfectants may be of value in preventing transfer of infection in situations where heavy soiling of linens is known to have occurred although at the present time use of chemical disinfectants is not recommended in hospital laundries.…”
Section: (Iii) Clothing and Household Linenmentioning
confidence: 99%
“…Survival of Staphylococcus aureus in linens after a 13 min machine washing at different temperatures and after drying. 0, Hot water/detergent wash; 0, hot waterdetergent wash with addition of 50-100 mg/l chlorine added(Walter & Schillinger 1975).…”
mentioning
confidence: 99%